Physical Qualities of International Female Rugby League Players by Playing Position. Issue 5 (May 2016) - Jones, Ben; Emmonds, Stacey; Hind, Karen; Nicholson, Gareth; Rutherford, Zoe; Till, Kevin
Abstract : Abstract: Jones, B, Emmonds, S, Hind, K, Nicholson, G, Rutherford, Z, and Till, K. Physical qualities of International Female Rugby League players by playing position and injury history. J Strength Cond Res 30(5): 1333–1340, 2016—The purpose of this study was to investigate the anthropometric, body composition, and fitness characteristics of female rugby league players by playing position. Data were collected on 27 players who were part of the English elite women's rugby league squad. Player assessments comprised anthropometric (stature and body mass), body composition (dual-energy X-ray absorptiometry) and fitness lower-body power (countermovement jump [CMJ], 20 kg jump squat [JS], and 30 cm drop jump), 5, 10, 20, 30, and 40 m sprint, 505 agility, Yo-Yo intermittent recovery test level 1 measures. Players were classified into playing position (i.e., forwards and backs) before analysis. A multivariate analysis of variance demonstrated significant ( p ⩽ 0.05) differences for body mass, stature, total fat, lean mass, and percentage body fat between forwards and backs. Positional differences were also observed for speed, agility, and lower-body power. Significant relationships were observed between total body fat and all fitness variables, and total lean mass was related to CMJ and JS peak power. This study provides comparative data for female rugby league forwards and backs. Body fat was strongly associated with performance and should therefore be considered in developing fitness characteristics. The relationship to match performance and trainability of these characteristics warrants further investigation.